Exploring the experiences of early adult fathers - Ignacio-Zambrano, Irene S. (Animo Repository, 2003)
This is an exploratory research on the life and experiences of early adult fathers. The main sources of data are the narratives of the young fathers describing their relationship with the mothers of their children prior to the conception of the baby and from the time they learned they were going to be fathers soon until their present condition of child caring. Eight respondents were gathered and they were required to be 19 to 25 years old residing within Metro Manila, Southern and Central Luzon with at least three years to three months experience of being fathers, and belonging to middle and upper socio economic classes. Narratives of their partners and significant others were also taken to further assess whether the narrations of the fathers were congruent with their reports. The narratives were categorized into themes according to the emergent responses. The results of the study showed that many of these young fathers are still financially dependent on their parents for raising their own family. Though they come from well to do families, monetary contribution is still a major concern. Lifestyles have likewise changed dramatically as well as the attitudes of these fathers particularly during the period when they learned of their partners' pregnancy. They are not fully prepared for the parenting roles they have assumed early in life. They consider the present moment as a period of adjustment for both the fathers and their wives. On being sons, they acknowledge their dependence on their family for financial support and of consulting their parents for decision making. They would like their children to be sent to good schools and acquire stable jobs. Most of the respondents and their partners and significant others admit their need for counseling intervention. Since the respondents either just graduated from college or about to finish their degree, they just came from the adolescent transition. Being fathers now would entail them to move on a faster phase for another transition on their young lives.